L’archeobotanica in Cina - Dal Martello, Rita; Dal Martello, Rita (Annali di Ca’ Foscari: Serie Orientale, 2025)
This study traces the development of archaeobotany in the context of Chinese Archaeology, with a particular focus on the analysis of macro-botanical remains from the early twentieth century to today. Although plant remains have been reported since the beginning of modern archaeological research in the country, the discipline became widespread and institutionalised only after the 2009 promulgation of the updated Field Archaeology Work Protocol, which mandated the collection of archaeobotanical remains in all archaeological excavations. This article outlines the main phases of development of the discipline – from initial chance discoveries to its institutionalization and subsequent internationalisation – and explores the reasons for its continued growth.